KAJIAN PRODUKTIVITAS TENAGA KERJA PADA PEKERJAAN STRUKTUR RANGKA ATAP BAJA (Studi Kasus proyek Peningkatan Sarana Ruang ICU, RSUD Raden Mattaher Jambi) - Elvira Handayani; Putri Syafira (Universitas Batanghari Jambi, 2018)
From the research results can be known the factors that affect the performance of the building. ICU Room Facilities, Jambi Provincial Hospital, the biggest is done by A21 on the first day that is equal to 91.771%. LUR level on the 2nd day, produced by A22 that is equal to 91,979%. While the level of LUR on the 3rd day generated by A9 of 91.146%. The predetermined variables are Education, Worker's Wage, Workers Health, Inter-Worker Relations, Managerial or Management, and Conformity of Use Simultaneous tools have no significant effect on the productivity of roof structure work. Partially or individually variables that have a significant influence on the energy level of work is the variable Work Experience and the variable of Conformity. Age / Age Comparison Variables have dominant influence on labor productivity level in the Improvement of Space Facility ICU RSUD Raden Mataher Jambi Province. Results of SPSS: 1) Test Validity, Based on the results of the study, can be concluded in 18 valid questions if r arithmetic> r table. And Variable Variable P12 is a variable that is not vailid, because this variable is not vailid because of the clarity of important question intentions, so the respondents have a big difference of perception and in the end cause the question becomes vailid; 2) Test Reliability, got all variables Cronbach's Alpha for test Reliability questionnaire can meet Cronbach Alpha value between 0.7-0.9, indicating the research questionnaire has a high Reliability value;3) Normality test, In the normality test, the researcher uses Shapiro-Wilk because the tested data is smaller than 50, whereas if more than 50, using the Kolmogorov-Smirnova part. Under the table of 4.27 above, the Index has the star number of Shapiro-Wilk test from 0.05 indicates normal distributed dataKeyword: Productivity